Analysis of The Selection of Ship Spare Parts Suppliers at PT. PTK Indonesia with an Analytic Hierarchy Process Approach - Wagimin; Kurnia, Wahyu Ismail (Journal of Sustainability Industrial Engineering and Management System, 2023)
This study aims to analyze the selection of ship spare parts suppliers at PT. PTK Indonesia uses the Analytic Hierarchy Process method. The research method used to select ship parts suppliers is the Analytic Hierarchy Process (AHP) method. The data collection technique was carried out by distributing questionnaires to 4 respondents. The questionnaire design consists of a comparative assessment of the importance of the criteria and each criterion. For data processing, the software used is Expert Choice. The results showed that the quality criterion was the most important selection criterion with a percentage of 55.8% (0.558) compared to other criteria. And PT. Askrindo is the most appropriate supplier to meet the demand of PT. PTK Indonesia has the highest importance presentation compared to other suppliers, which is 55.3% (0.553). The limitations of this study lie in the number of respondents, who only amounted to 4 companies (people), the number of criteria used to select suppliers, and the field of supplier selection. Meanwhile, the implications of the results of this study are in the form of determining criteria and potential suppliers that can be used by the Company to meet the needs of ship spare parts for PTK Indonesia. The origin of this research lies in case studies and the use of the AHP method as a decision-making tool in choosing criteria and potential supplier companies appropriately in meeting the needs of ship spare parts at PT. PTK Indonesia.